A Review of Quality Management Systems in South African HIV-AIDS Programmes: A Pre-Requisite for Sustainable Health Delivery - Ganesh, Shayhana; Rampersad, Renitha; Dorasamy, Nirmala (Journal of Economics and Behavioral Studies, 2017)
The global commitment to end HIV-AIDS is a bold one; requiring a multi-sectoral response strongly embedded within effective HIV-AIDS prevention efforts, patient advocacy and effective healthcare programme delivery. UNAIDS estimates that, of the 36.7 million individuals infected with HIV-AIDS globally, 19.1 million reside in South Africa (UNAIDS Gap report, 2016).In addition, approximately 2.1 million new HIV infections occurred in 2015 with almost 960 000 of those occurring in South Africa signalling that the rates of infections are not dropping as expected (UNAIDS Gap report, 2016). Given the unrelenting nature of this disease burden, even greater efforts are now required to turn the tide on HIV-AIDS globally, but more so in South Africa. These efforts entail more effective HIV-AIDS service delivery with combination prevention modalities, access to HIV-AIDS treatment and care, harm reduction of HIV-AIDS stigma and discrimination together with HIV-AIDS education, awareness and advocacy. Enhancing HIV-AIDS service delivery requires strong commitment with implementation of quality management systems in programme service delivery resulting in sustainable, effective and well run HIV-AIDS programmes. Quality management systems in HIV-AIDS programmes allow programmes to successfully meet their objectives thus allowing optimal patient care through effective and efficient means. To date there has been minimal implementation of quality systems in healthcare especially in South Africa. The use of health quality tools and systems in HIV-AIDS programmes locally and globally will allow for efficient and cost effective benefits for the optimal wellbeing of all those affected and infected by HIV-AIDS. This article reviews available data on the prevalence of quality management systems in HIV-AIDS healthcare and identifies gaps and smart practises towards recommendations for comprehensive global HIV-AIDS standards development.